All your perfects : a novel - Hoover, Colleen (New York : Atria Paperback, 2018)
The #1 New York Times bestselling author of It Ends with Us--whose writing is "emotionally wrenching and utterly original" (Sarah Shepard, New York Times bestselling author of the Pretty Little Liars series)--delivers a tour de force novel about a troubled marriage and the one old forgotten promise that might be able to save it. Quinn and Graham's perfect love is threatened by their imperfect marriage. The memories, mistakes, and secrets that they have built up over the years are now tearing them apart. The one thing that could save them might also be the very thing that pushes their marriage beyond the point of repair. All Your Perfects is a profound novel about a damaged couple whose potential future hinges on promises made in the past.
Keywords: FAMILY LIFE; PSYCHOLOGICAL; WOMEN; ROMANCE FICTION